The Role of Stressful Life Events among Women Experiencing Homelessness: An Intragroup Analysis. Issue 3 (26th November 2020) - Rodriguez‐Moreno, Sara; Panadero, Sonia; Vázquez, José Juan
Abstract: The aim of this study is to examine stressful life events (SLEs) among homeless women and how SLEs were related to patterns and trajectories of homelessness. Specifically, the study aimed to replicate and build upon by Muñoz et al. (2005) by using cluster and discriminant analysis in a sample of 116 homeless women. The sample was classified based on SLEs, and the relationship between the resulting subgroups and sociodemographic characteristics, homeless trajectories, physical and mental health, and social support was examined. The results suggest that the three‐cluster solution was theoretically and structurally meaningful: (a) the "Shorter homelessness trajectories and best health and mental health" subgroup was characterized by low levels of SLEs, a shorter homeless trajectory, lower prevalence of physical and mental health problems, and lower rates of alcohol and substances consumption; (b) the "Early onset of homelessness and poorer health and poorer mental health" subgroup was characterized by a higher prevalence of childhood and adolescence SLEs, an early onset of homelessness and greater chronification, mental health problems, and alcohol consumption; and (c) the "Chronic homelessness and poorest health and mental health" subgroup was mainly characterized by a higher prevalence of typically adulthood SLEs, as well as some SLEs that may be unique to women, a greater number of periods of homelessness, physical health problems, disabilities, and substance misuse. Increased knowledge about the different subgroups and trajectories of homeless women, as well as their specific characteristics and needs, will help us design social services and policies sensitive to all these differences. Highlights: Homeless women are especially vulnerable to stressful life events (SLEs). The Cluster A was characterized by low levels of SLEs. The Cluster B was characterized by childhood and adolescence SLEs. The Cluster C was characterized by typically adulthood‐ and women‐specific SLEs. Initiatives to help homeless women should be sensitive to these subgroup differences.